Bioengineered Nanoparticles Loaded-Hydrogels to Target TNF Alpha in Inflammatory Diseases - Isabel Matos Oliveira; Diogo Castro Fernandes; Fátima Raquel Maia; Raphael Faustino Canadas; Rui Luís Reis; Joaquim Miguel Oliveira (Pharmaceutics, 2021)
Rheumatoid Arthritis (RA) is an incurable autoimmune disease that promotes the chronic impairment of patients’ mobility. For this reason, it is vital to develop therapies that target early inflammatory symptoms and act before permanent articular damage. The present study offers two novel therapies based in advanced drug delivery systems for RA treatment: encapsulated chondroitin sulfate modified poly(amidoamine) dendrimer nanoparticles (NPs) covalently bonded to monoclonal anti-TNF α antibody in both Tyramine-Gellan Gum and Tyramine-Gellan Gum/Silk Fibroin hydrogels. Using pro-inflammatory THP-1 (i.e., human monocytic cell line), the therapy was tested in an inflammation in vitro model under both static and dynamic conditions. Firstly, we demonstrated effective NP-antibody functionalization and TNF-α capture. Upon encapsulation, the NPs were released steadily over 21 days. Moreover, in static conditions, the approaches presented good anti-inflammatory activity over time, enabling the retainment of a high percentage of TNF α. To mimic the physiological conditions of the human body, the hydrogels were evaluated in a dual-chamber bioreactor. Dynamic in vitro studies showed absent cytotoxicity in THP-1 cells and a significant reduction of TNF-α in suspension over 14 days for both hydrogels. Thus, the developed approach showed potential for use as personalized medicine to obtain better therapeutic outcomes and decreased adverse effects.